Sweet Unbinding: Sugarcane Cultivation and the Demise of Foot-Binding - Nora Cheng; Elliott Fan; Tsong-Min Wu (Institute of Labor Economics (IZA), 2021)
This study investigates the sudden disappearance of foot-binding, a costly custom practiced for centuries in China and Taiwan prior to its demise. We estimate the numbers of women who unbound their feet in response to the rapid growth of the sugarcane cultivation in Taiwan in the early 20th century, growth which boosted the demand for female labor relative to male labor. Cross-township variations based upon multiple history datasets indicate that cane cultivation had a strong and robust effect on unbinding. The IV estimations utilizing cane railroads – lines built exclusively for cane transportation – support a causal interpretation of the estimated effect. This finding implies that a change in gender-specific labor productivity can help eliminate costly norms against women, and it also provides additional support for the argument that foot-binding was incentivized by economic motives. We also present evidence lending credit for the conventional hypothesis of foot-binding as a form of marriage competition.
Keywords: J16; N35; Z13; 330; foot-binding; social norms; gender roles; sugarcane